Pengaruh Aktivitas Menghafal Juz’amma terhadap Kecerdasan Spiritual Anak di TPA Nurul Ilham Desa Taraman Jaya - Nurjanah, Siti; Yuniarti, Yuniarti (YASIN, 2021)
The sampling technique used saturated sampling with a sample size of 35 children. Based on the results of the research, it is known that the Juzz 'Amma memorization activity at TPA Nurul Ilham is in the moderate category, namely with a percentage of 60% with the number of frequency of children, namely 21. The spiritual intelligence of children at TPA Nurul Ilham is in the moderate category, namely with a percentage of 65.72% with The number of children's frequencies is 23. There is an effect of Juz 'Amma memorization activity with the spiritual intelligence of children at TPA Nurul Ilham, the cxy value is 0.63 with a chitung value of 23.7 then compared with ctabel with a significant level of 5% = 9.488 and a level of 1% = 13.277 determines that chitung> ctabel is 23.7> 13,277> 9,488 so it can be seen that the effect that occurs between Juzz 'Amma's memorization activity on the spiritual intelligence of children at TPA Nurul Ilham is in the moderate category.